MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SAINS POKOK BAHASAN BUMI DAN ALAM SEMESTA MELALUI PEMBELAJARAN PENEMUAN TERBIMBING PADA SISWA KELAS VI SDN 004 BONTANG - Sabina Sabina (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study is aimed at seeing the effectiveness of Guided Discovery teaching techniques to improve learning activity and learning mastery on science subject, entitled the World and the Globe.  The study uses classroom action research with two cycles. Each cycle in this study implements two meeting to do the actions.  The subject of this study is the sixth grade students of SDN 004 Bontang whose number is 44 students. Data were collected using observation and test.  This study discovers that learning activities improve from the first to the second cycle individually and in group.  In addition, the mastery on the subject matter also increases from the lower to the higher. At the end of the cycle, 90,01% students achieve improvement.  This means that Guided Discovery teaching techniques  to improve students activity and the mastery is proved in this study.